Race, rhetoric, and technology : searching for higher ground - Banks, Adam J. (Adam Joel) (NCTE-LEA research series in literacy and composition., 2006)
Examines moments in traditions of appeals, warnings, demands, and debates to make explicit the connections between technological issues and African Americans' equal and just participation in American society. This volume is intended for researchers, professionals, and students in Rhetoric, Computers and Composition, and African American Studies.